Swallowing, voice and quality of life of patients submitted to extended supratracheal laryngectomy - Zica, Guilherme Maia (Einstein (Sao Paulo), 2020)
OBJECTIVE: To describe functional and quality of life results after extended supratracheal laryngectomy. METHODS: In the period from September 2009 to January 2018, 11 male subjects were submitted to extended supratracheal laryngectomy. Swallowing abilities were assessed through videofluoroscopy and the clinical scale Functional Communication Measures of Swallowing. The voices were classified by means of the perceptual-auditory analysis Consensus Auditory-Perceptual Evaluation of Voice. All subjects completed a self-assessment questionnaire for voice and swallowing. RESULTS: Aspiration was found in four patients and all presented stasis in different structures. All subjects in this study were exclusively orally fed and hydrated. In the evaluation of quality of life in swallowing, patients had mean >80 in all areas (83.47 mean of scores). The general degree and the presence of roughness were the highest means present in Consensus Auditory-Perceptual Evaluation of Voice (37.81 and 49.36, respectively). The mean of 33.36 (±22.56) had little impact on quality of life under the perspective of vocal aspects. CONCLUSION: After supratracheal laryngectomy, swallowing was sufficiently restored and the quality of life was satisfactory. The voice presents severely impaired quality and preserved oral communication, with low impact on the activities of daily living. All individuals who maintained two cricoarytenoid units presented better functional results in swallowing and voice.